The Effectivness Of Using Xmind Application In Developing Students’ Writing Skill In Analytical Exposition Text At SMA Perintis 1 Bandar Lampung - Felicia Diza Valdivia Novalis; Dameria Magdalena Sidabalok (International Journal of Education, Vocational and Social Science, 2024)
This study investigates the effectiveness of utilizing the Xmind Application as a tool for enhancing students' writing skills, specifically in the genre of analytical exposition text. The research was conducted at SMA Perintis 1 Bandar Lampung, focusing on the impact of integrating Xmind Application into the writing instruction process. The research employed a quasi-experimental design, with a pre-test and post-test control group to assess the writing performance of students. A sample of students was selected, and they were divided into two groups: the experimental group, which received writing instruction using the Xmind application, and the control group, which followed traditional writing instruction methods. The findings reveal a significant improvement in the writing skills of students who were exposed to the Xmind Application. The application's visual mapping and organizational features contributed to a more systematic development of ideas and arguments in analytical exposition texts. Moreover, students in the experimental group demonstrated increased engagement and motivation in the writing process.